Geographic variation in reproductive traits and germination-niche dynamics in conservation-dependent Banksia arborea populations restricted to banded ironstone formations - Anderson, N.S.; Tudor, E.P.; Turner, Shane R.; Tomlinson, S.; Lewandrowski, W. (2024)
The temperature and moisture requirements for reproduction (i.e. seed production and germination) underpin the biogeographical relationships between climate, distribution and population dynamics of plants, particularly narrow range endemic species. We aimed to investigate reproductive outputs and the responses of seeds to temperature and moisture availability across three Banksia arborea populations that are distributed over a narrow range (< 200 km2) of semi-arid habitat on banded ironstone formations of Western Australia. We conducted reproductive trait assessments by quantifying follicles per cone, proportion of viable seed and associated seed mass followed by hydrothermal germination assessments for each population to characterise temperature and water stress tolerance. We found the southern-most population, that receives marginally higher rainfall, had heavier seeds (10 ± 0.02 mg), a cooler optimum temperature (16.1 °C) and wider germination capacity under water stress at 10 °C and 15 °C (Ψb50 = -0.66 to -0.87 MPa) compared to the two northern populations (Ψb50 = -0.60 to -0.65 MPa). By contrast, both northern populations had slightly warmer optimum temperatures for germination (16.9–17.5 °C) and a higher capacity to germinate under water stress at warmer temperatures of 22.5 °C (Ψb50 = -0.43 to -0.56 MPa, compared to -0.29 MPa). Our work highlights that, even within the specific requirements of a narrow range endemic, different populations adapt to marginally different temperature and water stress tolerances. Warming of the southern populations could impact on future recruitment, and conservation action to promote resilient ecosystems are suggested.